The effect of school climate and academic buoyancy on well-being and school success of high school students - Vrdoljak, Gabrijela (Primenjena psihologija, 2024)
Theories of positive youth development look at young people through their strengths and potentials. They state that these potentials will be maximally utilized if there is a supportive and stimulating environment. Given that young people spend a large part of their time in schools, the school environment is important for positive development. The aim of this research was to effect of school climate and academic buoyancy on the well-being and school success of high school students. The research was conducted on 3102 second-grade high school students from eight Croatian cities. The following instruments were used in the research: Croatian School Climate Questionnaire for Students (HUŠK-U), Academic Buoyancy Scale (ABS), Warwick-Edinburgh mental well-being scale (WEMWBS), and assessment of school success at the end of the last school year. The questionnaires were administered in an online version via the SurveyMonkey platform. Path analysis was used in data processing. First, the fit of the data to the proposed model was checked, and it was confirmed that the data fit the model. The results showed that the school climate has a significant positive effect on: academic buoyancy, well-being, and school success. Academic buoyancy has a significant positive effect on well-being, and a significant (although quite low) negative effect on school success. Academic buoyancy proved to be a significant mediator in the relationship between school climate and well-being and school climate and school success. The results indicate the importance of the school and the school environment in achieving positive outcomes for high school students. Also, it is important for the well-being of adolescents that they are not under a lot of stress due to tests and grades. What is problematic (although it is a small effect) is the finding that those who are under more stress about tests and grades achieve better school success.